1982
DOI: 10.3987/r-1982-03-0559
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Heterocyclic Diazo Compounds

Abstract: The preparation, chemical properties and synthetic utility of nitrogen heterocyclic diazo compounds are reviewed. IBTRODUCTIOB : Heterocyclic diazo compounds (1) and their diazonium salts (2) are versatile reagents and their chemistry ha8 received a considerable recent attention!" However, in spite of their interesting synthetic potentialities, the chemistry of this class of compounds has been ignored in available organic chemistry bocks. Moreover, with exception of Tedder's chapter in "Advances in Heterocycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Di azo tised aminopyrazoles have been re ported to re act with ac tive meth y lene re agents to yield ei ther hy dra zones which readily cyclise into pyrazolo [5,1-c] [1,2,4]tri azines or di rectly into the cy clic prod uct via a cycloaddition re ac tion un der the cou pling con di tion. 14,15 It has been found that diazotization of 2 af fords diazonium salt 19 which was coupled with ethyl cyanoacetate to yield a com pound of mo lec ular for mula C 12 H 15 N 5 O 5 S (M + = 325 m/z). The IR spec tra showed ab sorp tion bands for both cyano and es ter car bonyl groups at = 2200 and 1725, 1710 cm -1 .…”
Section: Scheme IImentioning
confidence: 99%
“…Di azo tised aminopyrazoles have been re ported to re act with ac tive meth y lene re agents to yield ei ther hy dra zones which readily cyclise into pyrazolo [5,1-c] [1,2,4]tri azines or di rectly into the cy clic prod uct via a cycloaddition re ac tion un der the cou pling con di tion. 14,15 It has been found that diazotization of 2 af fords diazonium salt 19 which was coupled with ethyl cyanoacetate to yield a com pound of mo lec ular for mula C 12 H 15 N 5 O 5 S (M + = 325 m/z). The IR spec tra showed ab sorp tion bands for both cyano and es ter car bonyl groups at = 2200 and 1725, 1710 cm -1 .…”
Section: Scheme IImentioning
confidence: 99%
“…93 Diazotization of 3-amino-1-phenylpyrazole (154) gave the corresponding diazonium salt 155 that reacted with 156 to yield 157 that was readily cyclized into 158 (Scheme 41). A novel green iodination of 3-aminopyrazole was described with iodine and hydrogen peroxide in water to give 4-iodo-3-aminopyrazole in 82% yield.…”
Section: Scheme 40mentioning
confidence: 99%
“…Diazotized aminopyrazoles have been reported to react with active methylene reagents to yield hydrazones, which either readily cyclize into pyrazolo[5,1‐ c ][1,2,4]triazines or directly into the cyclic product via a cycloaddition reaction under the coupling conditions . It has been found that diazotization of 5‐aminopyrazole derivative 6 affords diazonium salt 34 , which was coupled with ethyl cyanoacetate to yield a compound, which was identified as ethyl 2‐cyano‐2‐(2‐(4‐(2‐(1‐(3‐methyl‐6‐phenylimidazo[2,1‐ b ]thiazol‐2‐yl)ethylidene)hydrazinecarbonyl)‐3‐(phenylamino)‐1 H ‐pyrazol‐5‐yl)hydrazono)acetate ( 35 ).…”
Section: Resultsmentioning
confidence: 99%